What Makes Them Stay? The Important Role of Employee Value Proposition in Retaining Frontliner Retail - Namira, Ananda; Pramesti, Muthia (Jurnal Ilmiah Manajemen & Bisnis, 2025)
Amidst massive digital disruption, the retail industry faces its highest employee turnover rate, making the retention of frontline workers—who are crucial for operations and customer experience—a pressing strategic issue. This study investigates factors influencing frontliners' intention to stay (ITS). It examines the influence of the Employee Value Proposition (EVP) on ITS, with the Psychological Contract (PC) and Perceived Organizational Support (POS) as potential mediators. Adopting a mixed-methods approach, this study surveyed 269 frontline workers, with quantitative data analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis was then deepened by qualitative interviews to provide a richer interpretation of the findings. The results reveal a key finding: the transactional aspect of the EVP, encompassing compensation and tangible benefits, significantly and positively influences the intention to stay. Conversely, relational aspects like the psychological contract and perceived organizational support were found to have no significant influence. Furthermore, PC and POS also proved ineffective as mediators in the relationship between EVP and ITS. This finding implies that for today's retail frontliners, concrete economic elements are more powerful drivers of loyalty than psychological bonds or emotional support. The study provides clear strategic guidance for retail managers to prioritize transactional incentives in their efforts to curb high turnover rates and enhance workforce stability.